1998
DOI: 10.1002/(sici)1097-4652(199807)176:1<206::aid-jcp22>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

CD44v3,8-10 is involved in cytoskeleton-mediated tumor cell migration and matrix metalloproteinase (MMP-9) association in metastatic breast cancer cells

Abstract: In the present study, we have employed a unique breast cancer cell line (Met-1, which was derived from a high metastatic potential tumor in transgenic mice expressing polyomavirus middle T oncogene) to study the role of CD44 variant isoform(s) in the regulation of metastatic breast tumor cell behavior. The results of reverse transcriptase-polymerase chain reaction, Southern blot, nucleotide sequencing, immunoprecipitation, and immunoblot analyses indicated that these cells express a major CD44 isoform (molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
1
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 254 publications
(164 citation statements)
references
References 45 publications
7
154
1
2
Order By: Relevance
“…Both MMP-2 and/or MMP-9 are associated with tumor metastatic processes, and the more malignant tumors generally have the more potent MMP-2 and/or MMP-9 activity in stimulating metastasis of tumors (Bourguignon et al, 1998;Shamamian et al, 2001). In addition, different kinds of kinases of cell signal pathways such as PI3K and MAPKs are known to be involved in MMP activation and cancer cell invasion (Tanno et al, 2001;Cho et al, 2007;Bocca et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Both MMP-2 and/or MMP-9 are associated with tumor metastatic processes, and the more malignant tumors generally have the more potent MMP-2 and/or MMP-9 activity in stimulating metastasis of tumors (Bourguignon et al, 1998;Shamamian et al, 2001). In addition, different kinds of kinases of cell signal pathways such as PI3K and MAPKs are known to be involved in MMP activation and cancer cell invasion (Tanno et al, 2001;Cho et al, 2007;Bocca et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was recently reported that CD44 regulates signal transduction, including cell-cell and cellmatrix interactions. 29,30) Takahashi et al 31) reported that cell invasion and cell migration were enhanced after the treatment of melanoma cells with a monoclonal antibody to CD44 and the up-regulation of matrix metalloproteinases. We therefore consider that loss or dysfunction of CD44 may play an important role in cancer invasion or metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction mechanism of CD44 with MMP-9 is not known, however, MT1-MMP utilizes the hemopexin-like domain for its interaction with CD44 (Mori et al, 2002). MMP-9 interacts with CD44 in invadopodia (Bourguignon et al, 1998). These are the same cellular structures, which also contain MMP-2 and α V β 3 complexes (Deryugina et al, 2001) together with MT1-MMP (Nakahara et al, 1997).…”
Section: Cell Surface Associations Of the Gelatinasesmentioning
confidence: 99%